Lumbar disc herniation associated with scoliosis in a 15-year-old girl: case report - Fernando Campos Gomes Pinto; Arthur W. Poetscher; Fausto Ricardo Erba Quinhones; Mário Pena; Mário Augusto Taricco (Arquivos de Neuro-Psiquiatria)
Intervertebral disc herniation is a rare condition in childhood and adolescence, although some cases have already been reported in the literature. We present the case of a 15 year-old-girl with low back pain and scoliosis. She had no previous history of trauma or collagen diseases. MRI showed L4-L5 and L5-S1 disc herniations and no further bone and structural changes. After two level discectomy, pain ceased and scoliosis improved, without further treatment. Based on her evolution and on what has already been reported in literature, we consider that scoliosis associated with disc herniation in young patients is most likely to be only an anthalgic position, not indicative of further structural changes.